2017
DOI: 10.3389/fpsyg.2017.01737
|View full text |Cite
|
Sign up to set email alerts
|

When and How Does Psychological Voice Climate Influence Individual Change Readiness? The Mediating Role of Normative Commitment and the Moderating Role of Work Engagement

Abstract: This research explores the linking mechanisms and conditional processes underlying the relationship between psychological voice climate and individual change readiness. In accordance with the social identity theory, we argued that normative commitment would mediate the relationship between psychological voice climate and individual change readiness; furthermore, work engagement would moderate the proposed indirect effect. Two-wave survey data were collected from 187 full-time employees in a government-owned in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
(92 reference statements)
1
11
0
5
Order By: Relevance
“…Apart from the above-mentioned findings, we also discovered that NU significantly and positively affects employee innovation behaviors (γ = 0.307, p < 0.001), as well as environmental-friendly behaviors (γ = 0.368, p < 0.001), respectively (please refer to Figure 1). Our results thus render empirical support to prior research that found that employees' NC is significantly related to their behavioral outcomes [39,40,[42][43][44], and, thus, underscores the important role of NC in organizations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Apart from the above-mentioned findings, we also discovered that NU significantly and positively affects employee innovation behaviors (γ = 0.307, p < 0.001), as well as environmental-friendly behaviors (γ = 0.368, p < 0.001), respectively (please refer to Figure 1). Our results thus render empirical support to prior research that found that employees' NC is significantly related to their behavioral outcomes [39,40,[42][43][44], and, thus, underscores the important role of NC in organizations.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, NC has been discovered to motivate employee citizenship and other positive behaviors [40][41][42]. Considering we have argued that CUs may significantly influence employees' NC as well as their innovative and environmentally-friendly behaviors, we follow the well-recognized commitment-behavior tandem connection [43,44], and further posit:…”
Section: Hypothesis 3 (H3)mentioning
confidence: 97%
See 2 more Smart Citations
“…Previous research has demonstrated that employee work engagement can enhance their participation and stimulate their best performance, thus supporting organizational goals (Lee, Wang & Liu, 2017). Work engagement is a condition whereby an individual has a positive and fulfilling attitude toward their duties, and is characterized by vigor, dedication and absorption.…”
Section: Introductionmentioning
confidence: 99%